William Fredy Pérez Toro, Alba Lucía Vanegas Yepes, Carlos Mario Álvarez Martínez. Estado de derecho y sistema penal. La emergencia permanente de la reacción punitiva en Colombia. Medellín, Biblioteca Jurídica Diké-IEP, UdeA, 1997 - Zapata, Julio González (Estudios Políticos, 1997)
Reseña